Youth Employment Mobility - experiencing (un)certainties in Europe - Jan Skrobanek; Tuba Ardic; Irina Pavlova (Social Work & Society, 2021)
Youth's international mobility has become a hot spot of public interest, political debate and the scientific research over the last 20 years. Many positive aspects are attributed to youth mobility, that it opens for educational, apprenticeship and employment-related opportunities, that it fosters personal, socio-cultural and economic development and that it thus supports choice, agency and freedom in the transition from youth to adulthood. However, this positive framing of youth mobility also meets key concerns like 'arrested adulthood', 'precarization, prolongation and fragmentation of transitions', increasing risks of 'uncertainty' and 'unpredictability'. In this paper, we focus precisely on this double dynamic of contemporary transitions in the context of international youth mobilities. Based on quantitative and qualitative data from the HORIZON 2020 project MOVE[1] we explore the 'risk-choice-freedom-paradox' engraved in contemporary youth mobility. Our data clearly show how options and freedom to become internationally mobile are intertwined with perceived and experienced risks, insecurities and uncertainties in the context of young people's international employment mobility and it points to individual strategies to cope with this paradox.   [1] MOVE has received funding from the European Union's Horizon 2020 research an innovation programme under Grand Agreement No. 649263.